Blockchain adoption in sustainable supply chains: Opportunities, challenges, and sustainability impacts across sectors - Rahim, Md Jawadur; Islam, Md. Jahidul; Nath, Subroto Deb; Rahim, Muhammad Ihsan Ibn; Yeasir, Ather (Goodwood Publishing, 2024)
Purpose: This research reviews blockchain technology's integration into modern financial systems, outlining its huge potential to bring about improvement in areas such as transparency, security, and operational efficiency. Based on the challenges of data integrity, fraud prevention, and reduction of intermediaries, the study assesses the transformational role of blockchain in financial institutions. Research Methodology: A mixed-methods approach was taken, where quantitative data from the surveys of 150 financial executives across different types of organizations were combined with qualitative insights from expert interviews. Such statistical analysis, complemented by thematic interpretation, could enable an integrated assessment of blockchain applications and related challenges in the financial sector. Results: The results reveal that blockchain significantly enhances the transparency and security of transactions, hence reducing fraud and manipulation of data. The respondents were very optimistic about the cost reductions due to the elimination of intermediaries. Yet, these are counterbalanced by barriers to wide diffusion, such as scalability issues, regulatory uncertainties, and technical integration complexities that reduce the full potential of blockchain. Limitations: The limitations of the study are the small sample size, which limits the generalization of findings. Further research with larger and more diverse samples is needed to investigate more comprehensively the impact of blockchain on the financial sectors. Contributions: The research, therefore, contributes to discourses on blockchain as a transformative finance technology, giving insights into useful strategic, policy, and technology issues. Novelty: It also presented both opportunities and challenges in view of realizing blockchain's role in digitizing financial ecosystems.